Modern Food Microbiology - Jay, J. M. (New Delhi Springer, 2014)
With thirty revised and updated chapters the new edition of this classic text brings benefits to professors and students alike who will find new sections on many topics concerning modern food microbiology. This authoritative book builds on the trusted and established sections on food preservation by modified atmosphere, high pressure and pulsed electric field processing. It further covers food-borne pathogens, food regulations, fresh-cut produce, new food products, and risk assessment and analysis.
Science
Keywords: Food Microbiology